Interlanguage Analysis as a Formative Assessment: English Educators’ Attitude - Morganna, Ruly; Budiman, Asep (Educalitra: English Education, Linguistics, and Literature Journal, 2022)
The purpose of this study is to find out how English educators in Indonesia feel about preparing higher-quality English teaching by performing an interlanguage analysis based on students' existing English language skills. Hence, this qualitative study was undertaken to evaluate the attitudes of 10 English educators in performing an interlanguage analysis. They were chosen specifically because they had prior expertise, ensuring that they were well-versed in the study's topic and that the data the shared would be clear. The research data were gathered by handing out semi-structured questionnaires to English educators. Despite certain particular and situational restrictions, the findings demonstrated that all English educators had a favorable attitude toward performing an interlanguage analysis of students' English ability from an emotional, behavioural, and cognitive perspective. This research is significant because it can guide English educators who want to enhance their teaching quality.